아라이(阿來) 시에 나타난 티베트 문화의 형상화 - 박남용; Park Nam Yong (중국연구, 2019)
The study aims to study the poetic figuration of Tibetan culture in his poems, focusing on the world of works by A-Lai(阿來), a leading Tibetan poet and novelist. The author analyzes on the cultural identity of various Tibetan imaginations and minorities contained in his poems, through the imagery of the life and culture of the Chinese minority appearing in his poems, centering on A-Lai's poetry. Chinese minority literature can be said to be the work of a minority-turned-author who creates it in Chinese or in each ethnic language. Broadly speaking, it could include expressing the culture and identity of minorities as writers from the Han tribe. However, there is a limit to many studies of minority literature created in each ethnic language because deciphering the works published in that national language is essential. Therefore, it has to be studied based on the creation of Chinese by writers from minority regions. I believe that there is a need to re-recognize the diversity of present-day literature and literature by reconstructing the contemporary writer and his work world from the perspective of a mutual batter's perspective on minority literature and culture, and to redefine the existing research trends and perspectives. His poems reflect various aspects of Tibet's life, culture, and power structure, but also the disintegration of traditional Tibetan society and culture and the transformation of a communist-ruled modern society. So his literary world was born out of deep reflection on the Tibetan minority culture. His literature reflects the world of minority literature as a member of the minority, unlike mainstream literature in China. Conclusion, It could be confirmed that A-Lai's poetry creation shaped the nature and grasslands of Tibet, the natural and cultural customs of the native village, the conscious world of Tibetans thinking about life and death, and the conflicting world according to the dissolution of traditional culture and influx of modern civilization.